PENGARUH LOCUS OF CONTROL DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KASUS PT.PEGADAIAN CABANG TENTE) - Ansyarif Ansyarif; Wulandari Wulandari (Jurnal Riset Rumpun Ilmu Ekonomi, 2022)
The  study aims to determine and analyze Locus Of Control and work environment on employee job satisfaction. The sampling technique used is saturated sampling where the sample used in this study is all members of the population as many as 32 employees. The methods used in this study are validity, reliability, classical assumptions, multiple linear regression, t-test and f-test. The results of the study partially revealed that the Locus Of Control had no effect and was not partially significant on job satisfaction, while the work environment variable had a partial and significant effect on job satisfaction.results of the simultaneous test say that the Locus Of Control and the work environment have a simultaneous effect on job satisfaction.